Formulation and Evaluation of Sodium Hyaluronate – Triphala Ophthalmic Emulsion for Treatment of Computer Vision Syndrome - Revankar, Hrithik Satish; Bhilegaonkar, Shilpa (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Computer vision syndrome is a eye condition linked to long periods of screen use. Early signs include irritation, redness and dryness. Chronic cases can lead to serious issues like high myopia, vitreous floaters and retinal detachment. The study is aimed to create ophthalmic emulsion based on Triphala Ghrita that has antioxidant, anti-inflammatory and tissue healing properties. Materials and Methods: The emulsion was made using Triphala Ghrita (oil phase), 0.1% sodium hyaluronate (aqueous phase), Tweens and spans (surfactant) and ethanol (co-surfactant). Six formulations were assessed physicochemical properties. Stability studies found that E3 was the most effective formulation. The pharmacological effects using antioxidant and anti-inflammatory assay were analyzed. In vitro permeation using eggshell membrane and cornea tissue was performed and finally histopathological studies were conducted to confirm the therapeutic ability of the formulation. Results: E3 formulation showed stable physicochemical properties and clear morphology. Antioxidant tests indicated the formulation has better antioxidant potency than the references used, also it was a potent anti-inflammatory agent as well. Permeation studies showed oil phase did not permeate eggshell membrane but using goat corneas the aqueous phase showed a CDR of 9.7% at 30 min and also the oil phase did permeate. Histological analysis confirmed rejuvenation of corneal tissue after treatment with emulsion. Conclusion: The optimized ophthalmic emulsion (E3) showed strong anti-oxidant, anti-inflammatory effects, effective corneal penetration and rejuvenation of corneal tissue which highlights its potentials as a treatment for ocular damage due to CVS
Keywords: Computer Vision Syndrome (CVS); Sodium hyaluronate; Triphala; 5-retinal disease; Cornea; Ocular damage; Screen; Emulsion